Personal Financial Management and Wealth Inequality in South Africa - Fortuin, Marlin Jason; Makoni, Patricia Lindelwa; Grebe, Gerhard Philip Maree (Acta Universitatis Danubius. Œconomica, 2022)
Like many developing countries, South Africa has persistently experienced high levels of wealth inequality since independence in 1994. Despite government policy formulated to address this problem, there has been almost no improvement to the wealth status of the country’s majority population. This study thus examines how personal financial choices influenced wealth inequality in South Africa over the period 2010 to 2019 using a behavioural life-cycle model. Despite a decrease in wealth inequality over this period, the extent of this decrease is almost negligible. Results show that the majority of South African households do not possess enough wealth for household decision-making on wealth allocation to have a meaningful impact in reducing wealth inequality through more efficient use of assets. South African households should prioritise increased allocation of resources to education in labour sectors that possess and foresee a critical shortage of skills in the future. Such labour sectors are characterised by stable and higher levels of income, which then provides a mechanism for the accumulation of wealth.